Investigations into the interactions of Heterodera Rostochiensis Woll., Rhizoctonia solani Kühn and Colletotrichum coccodes (Wallr.) Hughes on the tomato plant and the effects of Aphelenchus avenae Bastion on these fungi - Roy, A. K. (The University of Edinburgh, 1970)
Investigations into the interrelationships of two nematodes, Heterodera rostochiensis and Aphelenchus avenae and two fungi, Rhizootonia solani and Colletotrichum coccodes on tomato (var. - Alisa Craig) were undertaken.

The plants suffered greater growth check when H. rostochiensis attacked before the fungi'than when the fungi preceded the nematode. Incidence of diseases due to the fungi and production of cysts of H. rostochiensis was also greater in the former treatment than the latter. Effects of simultaneous inoculation of fungi and nematode lay between these two treatments. The fungi retarded the formation of giant cells by H. rostochiensis and therefore, development of cysts decreased. The fungi depressed the hatching of larvae from cysts but did not affect entry of the larvae into roots. On the other hand, if the nematodes could produce giant cells before fungus invasion these were favoured by the fungi for colonization.The nematodes were found to possess some indole derivative/s in their bodies.

Though R. solani grew better at 27°C in P.D.A. and at 23°C in sterilized soil than at lower temperatures but the rate of growth at these higher temperatures dropped quickly. The survival capacity of R. solani in sterilized soil declined considerably at 25°C and was almost nil after 8 months. On the contrary, it perpetuated much better at 6 + 2°C. Variability in the growth rate as well as in cultural characters were noticed among different iiisolates of R. solani.

A. avenae multiplied more rapidly in R. solani than C. coccodes culture but no significant difference in any of the morphometric values was observed. Number of eggs laid per female was more in R. solani than C. coccodes but no significant difference was found in the length of egg laying period.

Incidence of diseases due to R. solani and G. coccodes was reduced by adding A. avenae in sterilized soil but not in unsterilized soil. Correspondingly the growth of the plants was also increased. A. avenae multiplied considerably in soil in the presence of fungus inoculum grown on sugarbeet seed but their number did not increase appreciably when the fungus added was grown on maize meal sand medium.